Pengembangan Ekonomi Lokal melalui Perencanaan Pembangunan yang Mengintegrasikan Smart Farming dan IoT - Rizki Ananda Putri; Alexanria Liana Crisvilia Way; Fatih Naufal; Silvester Satrio Langobelen; Arina Romaina; Ardieansyah Ardieansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Local economic development plays a crucial role in strengthening regional independence and improving community welfare. One emerging approach is the integration of smart farming and the Internet of Things (IoT) within development planning, particularly in the agricultural sector. This study aims to analyze how the integration of smart farming and IoT contributes to local economic empowerment through production efficiency, value-added improvement, and the creation of new economic opportunities. The research employs a literature review method by examining recent national and international studies relevant to this topic. The findings indicate that the application of smart farming technologies can improve resource efficiency by up to 50%, reduce pesticide use by around 60%, and increase crop productivity by approximately 30%. Beyond its economic impact, IoT adoption also fosters social transformation in rural areas through enhanced digital literacy and farmer independence. However, several challenges remain, including limited digital infrastructure, high initial investment costs, and technological literacy disparities among regions. Therefore, the successful implementation of smart farming and IoT requires strong multi-sector collaboration among governments, academic institutions, private actors, and local communities to ensure sustainable innovation that effectively contributes to regional economic growth.